Biodegradable electrospun fibers for drug delivery application - Azila Azura, Juma'at (2010)
The combined use of two techniques namely electrospray and spinning is made use in a highly versatile technique called electrospinning (electro+spinning). Controlled drug delivery systems have gained much attention in the last few decades. This is due to the many advantages compared with the conventional dosage forms such as improving therapeutic efficacy and reducing toxicity by delivering them at a controlled rate to the specific site. The objective of this research is to study the drug release behavior from the electrospun scaffolds and its antimicrobial effects on microbacteria culture. Non-steroidal anti-inflammatory drug (NSAID) was embedded in two types of polymer; polylactide acid (PLLA) and polycaprolactone(PCL) with the parameters of drug concentration; 5% of indomethacin concentration and no indomethacin concentration (control), and types of microbacteria used; E.coli sp., B.cereus sp., and M.luteus sp. All the microbacterial cultures were incubated for an overnight at 37°C. Results showed throughout the study, the absorbance for polymer with no drug concentration is higher than polymer with 5% of drug concentration as there is no drugs diffuse from the polymer to inhibit the microbial growth. The growth of microbacterial can be visualized directly from the plate to assess the viability of indomethacin release. In this study, it is clear that these PLLA and PCL-with indomethacin based electrospun scaffolds hold a future potential in drug delivery system.